IMPLEMENTASI METODE SMART UNTUK PEMILIHAN PEGAWAI BERPRESTASI PADA PUSKESMAS SEI DADAP - safii, muhammad; Ihsan, Fuadi Aula; Persadanta, Marwarizmi Al Zizzul; Maulana, Rizqy; Afrisawati, Afrisawati (LPPM STMIK Royal Kisaran, 2024)
Abstract: Sei Dadap Community Health Center has a central role in providing health services in its area. Focusing on employee performance as the main determinant of service effectiveness and quality is important. This research aims to develop a decision support system to support Community Health Center leaders in selecting employees who excel. Research methods include identifying assessment criteria with the leadership of the Community Health Center, collecting employee performance data, and implementing a decision support system using the SMART Method for data analysis. Evaluation of system results is carried out to ensure consistency and accuracy. The implementation of the research results is directed at the HR management of the Community Health Center, with recognition and promotion for outstanding employees, as well as guidance for those who need it. This research provides a basis for Sei Dadap Community Health Center leaders in making decisions regarding employees, while increasing the transparency and efficiency of HR management. In this system, users can enter employee data as well as employee assessment results for each relevant criterion.The system will display the decision results in the form of employee rankings based on ranking. Keywords: Decision Support System; Employee Achievement; SMART.Abstrak: Puskesmas Sei Dadap memiliki peran sentral dalam memberikan layanan kesehatan di wilayahnya. Fokus pada kinerja pegawai sebagai penentu utama efektivitas dan kualitas layanan menjadi penting. Penelitian ini bertujuan mengembangkan sistem pendukung keputusan untuk mendukung pemimpin Puskesmas dalam memilih pegawai yang berprestasi. Metode penelitian meliputi identifikasi kriteria penilaian dengan pimpinan Puskesmas, pengumpulan data kinerja pegawai, dan penerapan sistem pendukung keputusan dengan Metode SMART untuk analisis data. Evaluasi hasil sistem dilakukan untuk memastikan konsistensi dan akurasi. Implementasi hasil penelitian diarahkan pada manajemen SDM Puskesmas, dengan pengakuan dan peningkatan bagi pegawai berprestasi, serta pembimbingan bagi yang membutuhkan. Penelitian ini memberikan landasan bagi pemimpin Puskesmas Sei Dadap dalam pengambilan keputusan terkait pegawai, sambil meningkatkan transparansi dan efisiensi manajemen SDM.Dalam sistem akan menampilkan hasil keputusan berupa peringkat pegawai berdasarkan ranking.Kata kunci: Sistem Pendukung Keputusan;Pegawai Berprestasi; SMART